2015
DOI: 10.1111/nep.12421
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II type 1 receptor antibody precipitating acute vascular rejection in kidney transplantation

Abstract: ABSTRACT:Atypical non HLA antibodies are increasingly recognised as causes of immunological injury in allotransplantation. In this report we describe a non HLA sensitized male renal allograft recipient who developed acute vascular rejection on a "for cause" biopsy (Banff v2, g2, ptc 3) at day 4 post first renal allograft in the presence of elevated angiotensin II type 1 receptor antibodies (AT1R-Ab level 14.1). The acute rejection was treated with pulse corticosteroid therapy, anti-thymocyte globulin (ATG × 6)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 8 publications
(20 reference statements)
1
19
0
Order By: Relevance
“…Our data show a high prevalence of AT 1 R‐Ab in subjects with TG. Indeed, the frequency of PT‐Ab positive patients was 16.5%, while the frequency of patients with PT‐Ab within the “at risk” range was 51.5%, according to previous studies describing a variability from 17% to 47% . On the other hand, we found lower frequency in AT 1 R‐Ab positivity (11.5%) or within the “at risk” range (27.4%) at the time of biopsy.…”
Section: Discussionsupporting
confidence: 72%
“…Our data show a high prevalence of AT 1 R‐Ab in subjects with TG. Indeed, the frequency of PT‐Ab positive patients was 16.5%, while the frequency of patients with PT‐Ab within the “at risk” range was 51.5%, according to previous studies describing a variability from 17% to 47% . On the other hand, we found lower frequency in AT 1 R‐Ab positivity (11.5%) or within the “at risk” range (27.4%) at the time of biopsy.…”
Section: Discussionsupporting
confidence: 72%
“…Dragun et al [8,13] have shown for the first time their involvement in patients presenting acute rejection episodes (ARE) with severe hypertensive crisis. Since this first observation, the correlation of anti-AT1R antibodies and acute rejection and/or graft failure has become more debated in kidney transplantation sometimes due to a lack of power of studies [15][16][17][18][19][20][21][22][23][24]. In 2013, we showed on a large monocentric cohort (n = 599) of French kidney recipients that patients who displayed a pretransplant AT1R-Ab level above 10 U/ml had higher risk of acute rejection episodes within the first month following transplantation and graft failure beyond 3 years post-transplantation [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…There are some reports in which TPE was used to treat AMR in kidney transplant recipients with AT1RAbs. Jobert et al reported a case of AMR in a kidney transplant recipient with AT1RAb, who received 6 TPE procedures with 1.5 plasma volume exchange . Fuss et al used 3–11 TPE procedure to treat 6 kidney AMR patients with AT1RAbs .…”
Section: Discussionmentioning
confidence: 99%
“…Jobert et al reported a case of AMR in a kidney transplant recipient with AT1RAb, who received 6 TPE procedures with 1.5 plasma volume exchange. 15 Fuss et al used 3-11 TPE procedure to treat 6 kidney AMR patients with AT1RAbs. 16 Lee et al 17 treated 11 cases of AT1RAb associated AMR with a combination of TPE and IVIG, sometimes followed by rituximab (9/12), antithymocyte globulin (5/12), or bortezomib (1/12).…”
Section: Discussionmentioning
confidence: 99%